Educação popular em Saúde: intervenção participativa na construção de relações dialógicas entre portadores de Diabetes MellitusAdulto (DM2) e profissionais - Damasceno, Cleide Ferreira (2003)
The present study, based on Paulo Freire ideas, had as its objective the investigation of methodological procedures that are suitable for work with Adults Diabetes Melitus Sufferers (DM2) Education. The study has as its main feature a Participative Intervention, in Culture Circles, which are tools capable of achieving the proposed objectives. The locus of the research was a Unit of Primary Health Attention, in the city of Fortaleza, Brazil. The field work was developed in the Culture Circles, by a group of twenty three DM2 Sufferers and a Researcher-Entertainer. In order to collect the data, the patients reports weres surveyed to get their addresses and complementary information; in addition, the selection of the group followed the criteria which were pre- established in the project. Thirty (30) home visits were done - the initial phase of the research, in which the speeches and the relevant themes were taken for culture circles of their interest. Besides the daily routines observation, in loco, these visits allowed the collective interviews with the families and the invitation for the DM2 sufferers to participate in the culture circles. In the period of three months and a half, thirteen (13) meetings were done in which the “generator” themes were explored; these were connected with the life experiences of the participants. The results were registered based on the participants’ statements show that their significant habit, costumes and posture changes in their daily lives. Besides, there is evidence that the development of pedagogical activities that dealt with the affectivity amongst the group was important for the diabetes sufferers and contributed to increase the self esteem of the DM2 sufferers. For the majority of the group the reading of the Bible represented a stimulus for living as a diabetic. By discovering themselves as “to be well-informed” they revealed themselves as confident and strong to face situations. The awakening to the learning about the disease should be facilitated by the professionals in the form of a dialogue. As one of the participants said, the interaction that leads to knowledge helps to “carry on with life”; the lack of knowledge and the small comprehension of what DM2 sufferers feel limits their living. I can also affirm that besides the enrichment of my professional life, the research contributes as subsidy for a work with a new methodology, where the professionals adopt the dialogue to the orientation of the DM2 sufferers. In order to achieving this, it is necessary to rethink the process of training these professionals, directing them to a reflexive, criticai and human posture. The research may contribute in two other ways: first, to the realization of training sessions for the health professionals who work at the unity where the study was carried out, to give continuity to the process with the use of the methodology built through the participative intervention, in culture circles; and second, to the possibility of developing training sessions for other professionals who deal with DM2 sufferers, in other health units.